(untitled) (Damascus University Journal of agriculture sciences, 2024)
An experiment was conducted in the agricultural scientific research center in Al-Qamishly, Al-Hasakah Governorate, during the 2021-2022 planting season, to study the effect of three planting dates (D1: mid-November, D2: first December, D3: mid-December) on some productivity and seed quality traits of three ecotypes of fenugreek were collected from three governorates in Syrian Arab Republic, namely: (G1: Hasakah, G2: Sweida, G3: Homs). The studied treatments were distributed in the experiment according to the randomized complete block design (RCBD) in the order of split plots, by 3 duplicates for each treatment. The results showed that there were significant differences between the studied treatments and their interactions, where the planting date (D2) excelled over the rest of the dates with all productivity traits, and achieved the highest significant value for each of: the weight of one thousand seeds (14.65 g), biological yield and seed yield (4536.97, 1525.13 kg .ha-1 respectively). The cultivation of the ecotype (G1) was significantly superior to the rest of the cultivated models with productivity traits: biological yield and seed yield (4062.2, 1286.31 kg .ha-1 respectively, and quality traits: protein percentage, fixed oil percentage, and alkaloids percentage in seeds (20.84, 8.43, 10.42 % respectively). As for the overlap of the studied treatments, the cultivation of the two ecotypes (G1 and G3) at the planting date (D2) gave the highest significant value for: biological yield (4586, 4547.1 kg .ha-1 respectively), seed yield (1570.27, 1536.79 kg .ha-1 respectively), and the harvest index (34.24, 33.79 % respectively), while the cultivation of the ecotype (G1) in the two dates (D2 and D3) gave the highest significant value for each of: the percentage of fixed oil (8.45, 8.53 % respectively), and the percentage of alkaloids (10.43, 10.47 % respectively).